Automated Testing of Mobile Applications using Scripting Technique: A Study on Appium (International Journal of Current Engineering and Technology, 2014)
Testing is an integral part of software engineering and preoccupies significant prerogative in product-based industry applications. Today, companies are spending increasing amount of time and resources in ensuring the application is fully tested for best user experience and optimum performance by the application, by manual testing. Testing is carried out to make sure that daily updates are reflected correctly. In this paper, automated testing for mobile applications, both hybrid and web, are discussed. This paper comprises of the technology used in testing the Graphical User Interface of Android and iOS applications using an open source mobile testing tool Appium. By replacing the manual testing by automated testing using scripting techniques can improve the effort per unit time and the accuracy per test case. Furthermore, a comparison between Appium and other Automated Testing tools is done to state the advantages of using Appium for mobile User Interface testing.
Keywords: Scripting techniques; mobile application; Appium; Automated testing; UI testing; iOS apps; Android apps